Rifamycin congeners kanglemycins are active against rifampicin-resistant bacteria via a distinct mechanism - James Peek; Mirjana Lilic; Daniel Montiel; Aleksandr Milshteyn; Ian Woodworth; John B. Biggins; Melinda A. Ternei; Paula Y. Calle; Michael Danziger; Thulasi Warrier; Kohta Saito; Nathaniel Braffman; et al. (Nature Communications, 2018)
Resistance to rifamycin antibiotics, which target bacterial RNA polymerases, is a growing problem. Here, the authors identify gene clusters from soil metagenomes encoding production of rifamycin analogues that are active against rifampicin-resistant bacteria through a distinct mechanism.